Observer based temperature control for reduced thermal cycling in power electronic cooling - Wang, Xiang; Castellazzi, Alberto; Zanchetta, Pericle (Elsevier, 2013)
This paper presents an advanced dynamic cooling strategy for multi-layer structured power electronic modules. A observer based feedback controller is proposed to reduce a power device or module's thermal cycle amplitude during operation, with the aim of improving reliability and lifetime. The full-state observer design is based on a developed Cauer type thermal model. The observer enables estimation and control of the temperature at reliability critical locations only measuring one accessible location. This makes the method particularly powerful and suitable for application in power systems. The designed strategy is confirmed experimentally. Although the experiment is developed for a specific application scenario, the proposed strategy is of general validity.